Efficacy and safety of afatinib in a Chinese population with advanced lung adenocarcinoma with sensitive EGFR mutations. Issue 6 (16th May 2019) - Wang, Shouzheng; Xing, Puyuan; Yang, Ke; Hao, Xuezhi; Ma, Di; Mu, Yuxin; Li, Junling
Abstract : Background: Afatinib is an irreversible ErbB family blocker that improves progression‐free survival (PFS) of advanced EGFR ‐mutant lung adenocarcinoma compared to chemotherapy. However, afatinib leads to more adverse events than first‐generation EGFR inhibitors. Hence, exploration of the optimal afatinib initial dose and its efficacy and safety in Asian patients has drawn extensive attention. Methods: We retrospectively evaluated demographic and clinical information, survival data, and adverse events in advanced non‐small cell lung cancer patients treated with afatinib from 27 February 2017 to 30 October 2018. Results: A total of 60 patients were included in the study. Thirty‐nine (65%) patients received afatinib as first‐line treatment. The median PFS was 12.3 months (95% confidence internal 7.6–17.0). Multivariate Cox regression analysis revealed that age, gender, smoking history, baseline brain metastasis status, afatinib starting dose, and mutation type did not significantly influence PFS. No significant difference in median PFS between patients treated with an initial dose of afatinib of 40 mg or 30 mg, either in the first‐line (14.5 vs. 5.2 months; P = 0.101) or in a second or later‐line setting (3.0 vs. 5.0 months; P = 0.375) was observed. The incidence of all grades of rash/acne (92.5% vs. 61.1%; P = 0.011) and paronychia (82.5% vs. 50.0%; P = 0.010) in the 40 mg group was significantly higher than in the 30 mg group. Conclusion: First‐line afatinib treatment is beneficial for advanced lung adenocarcinoma patients with sensitive EGFR mutations. Initial dose and baseline brain metastasis status do not significantly impact PFS.